SmartCoding: An online platform for estimating political parties' policy positions - Djouvas, Constantinos; Gemenis, Kostas (My University, 2019)
We present a platform to estimate parties' (or candidates') positions in an 'iterative expert survey' approach based on the Delphi method commonly used in forecasting. In terms of architecture, our challenge was to build a web-based system that allows handling of the estimates provided by a panel of expert coders in a distributed and asynchronous manner using the principles of anonymity, iteration, and statistical aggregation. We describe the system built for recording and presenting all the relevant information to the coders over multiple rounds with feedback from each round to subsequent ones, as well as a module for identifying consensus among coders. Finally, we discuss improvements that can be implemented to adapt the platform in cross-national research as well as estimation problems outside the field of application illustrated in this paper.
Keywords: Databases; Delphi; Software Development; Web Technologies